The Changing Role of Customer Experience in the Age of Industry 4.0 - Rekettye, Gábor; Rekettye Jr., Gábor (Marketing & Menedzsment, 2020)
THE AIMS OF THE PAPER The fourth industrial revolution will result in a paradigm shift in the production and the marketing of products and services. The digitalization driven paradigm shift will make it possible to personalize the marketing tools, like pricing, distribution, communication, customer management, and customer experience. The aim of the paper is twofold: firstly to draw attention to the increased importance of customer experience and secondly to discuss how customer experience has changed due to the digitalized business environment. METHODOLOGY The conceptual study builds on a comprehensive literature review. The literature studied includes scientific papers describing how customer experience has developed and altered in different industries. The desk research also took into consideration the published finding of researches carried out by well-known international research agencies. MOST IMPORTANT RESULTS One of the most important results of the study is to find an appropriate definition of customer experience and to find its role among the managerial functions. Another result is the knitting of customer experience to the development of the consumer decision journey. Digitalization has completely changed the traditional funnel type of the customer decision journey, new touchpoints have appeared and gained importance. The paper discusses the role of customer experience management and elaborates on the process of how companies should prepare their activities in this field to enhance their competitiveness. RECOMMENDATIONS The study concludes that companies to stay competitive have to map the decision journey of their existing and potential customers. They have to explore the important contact point and have to provide them with authentic content and information. This is rather difficult in today’s multichannel environment. The real-time information they need should be provided through the analytics of big data. While collecting this information they should take care not to hurt the privacy of customers.